2020
DOI: 10.1177/0954407019899507
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement and flow field investigation in hydraulic torque converter based on a new design of segmented blades

Abstract: Hydraulic torque converter is of lower efficiency in the powertrain, particularly at low speed ratio, which is crucial for vehicles due to its ability of torque multiplication. Therefore, torque converters should be taken into account with both higher start-up acceleration and transmission efficiency. Inspired by the fact that the multi-airfoils of the aircraft can improve the lift, a new design of segmented turbine blade in torque converter is presented to improve the transmission efficiency and start-up acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Schweitzer and Gandham [10] conducted an analysis of a working fluid flow within the HTC using CFD methods, and the results of the numerical calculations are verified on a test station using laser Doppler velocimetry LDV. Similar research is shown in the studies [11,12,13,14,15,16,17]. The study [18] shows an optimization of the selection of the entry angle for a pump rotor and the entry angle for a turbine rotor in a HTC.…”
Section: Literature Reviewsupporting
confidence: 70%
“…Schweitzer and Gandham [10] conducted an analysis of a working fluid flow within the HTC using CFD methods, and the results of the numerical calculations are verified on a test station using laser Doppler velocimetry LDV. Similar research is shown in the studies [11,12,13,14,15,16,17]. The study [18] shows an optimization of the selection of the entry angle for a pump rotor and the entry angle for a turbine rotor in a HTC.…”
Section: Literature Reviewsupporting
confidence: 70%
“…Therefore, according to a certain time step size (0.0005 s), the pump and turbine rotate along the gird interface during the calculation. In addition, as shown in Table 2, the other parameters of the CFD model in the ANSYS fluent were set (Liu et al, 2020). The solution was assumed to have converged when the monitored turbine torque tended toward stability, and the defined residuals for all equations were less than 1E-4.…”
Section: Computation Settingsmentioning
confidence: 99%
“…The performance prediction was the key task for HTC design in industry, so another HTC was presented to further testify SBES models, as shown in Figure 16. This product, whose geometry could be found in our previous study (Liu et al, 2018c(Liu et al, , 2020 in Figures 16(a), 16(b) and 16(c), was subjected to the numerical simulation, and the external characteristics could be extracted from the simulation results. Before the calculation, the grid dependence was investigated; however, we did not include it in this study due to space/word constraints.…”
Section: Analysis Of Thermal Flow Fieldmentioning
confidence: 99%
See 1 more Smart Citation